2020
DOI: 10.4094/chnr.2020.26.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Infant Care Education Program for Mothers of Late-preterm Infants on Parenting Confidence, Breastfeeding Rates, and Infants' Growth and Readmission Rates

Abstract: Purpose: The purpose of this study was to evaluate the effects of an education program for mothers of late-preterm infants on parenting confidence, breastfeeding rate, and infants’ growth and readmission rate.Methods: The participants were 53 mothers of late-preterm infants (26 in the experimental group and 27 in the control group). The experimental group was administered the late-preterm care education program while the control group received standard care. The program consisted of two sessions during hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 21 publications
5
29
1
1
Order By: Relevance
“…Specifically, 50% of the LPIs in both groups in the study by Jang and Hong [17] were recruited from a nursery and had relatively fewer health issues, whereas the LPIs in this study were recruited from the NICU alone. This result also aligns with that reported by the study of Jang and Ju [20], which provided the mothers of 53 LPIs with an infant care education program focused on promoting breastfeeding and demonstrated a significantly higher breastfeeding rate (73.1%) in the experimental group (n=26) at 1 month after discharge than in the control group (40.7%; n=27). Moreover, an integrated review of 13 breastfeeding education interventions for LPIs suggested that most interventions had positive effects on establishing exclusive breastfeeding [2].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, 50% of the LPIs in both groups in the study by Jang and Hong [17] were recruited from a nursery and had relatively fewer health issues, whereas the LPIs in this study were recruited from the NICU alone. This result also aligns with that reported by the study of Jang and Ju [20], which provided the mothers of 53 LPIs with an infant care education program focused on promoting breastfeeding and demonstrated a significantly higher breastfeeding rate (73.1%) in the experimental group (n=26) at 1 month after discharge than in the control group (40.7%; n=27). Moreover, an integrated review of 13 breastfeeding education interventions for LPIs suggested that most interventions had positive effects on establishing exclusive breastfeeding [2].…”
Section: Discussionsupporting
confidence: 91%
“…There were more hospital visits in this study than reported by Tomashek et al [5], according to whom 4.3% of LPIs were likely to be readmitted or had an observational stay of less than 24 hours in hospitals. In addition, Jang and Ju [20] stated that none of the LPIs in the group provided an infant care education program for LPIs were readmitted, whereas one of the LPIs (3.7%) in the control group was readmitted due to enteritis. Of particular note, the feeding methods of the seven LPIs who visited hospitals were formula feeding for three infants, mixed feeding for three infants, and breastfeeding for one infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 38.5% of any breast milk feeding in this study was lower findings of previous studies reporting 63.8% of breastfeeding at one month postpartum in LPIs [7] and 75.4% of breastfeeding at six weeks in UK LPIs [19]. This finding was also lowered 40.7% of breastfeeding at one month after discharge in LPIs who did not receive a breastfeeding education [12]. Above all, less than 10% of exclusive breastfeeding in this study was far lower than the international recommendation for breastfeeding by the World Health Organization [10].…”
Section: Discussioncontrasting
confidence: 85%
“…Os autores destacam que a aquisição de conhecimento é muito mais eficaz quando o sujeito participa ativamente do processo de aprendizagem, ao invés do uso de métodos unidirecionais. Além disso, encontraram que a taxa de aleitamento materno no primeiro mês após a alta foi de 73,1% no grupo experimental, que recebeu as intervenções (14). Resultados de pesquisa convergente assistencial, com seis mães de bebês internados em unidades neonatais de um hospital de Maringá, ratificam a importância da adoção de protocolo de orientação para a alta do RNPT, como estratégia para a sistematização da assistência em direção à conquista da autonomia materna no cuidado ao filho, bem como para a padronização de condutas da equipe de saúde.…”
Section: Discussionunclassified